Identifying KLF14 as a potential regulatory factor in liver regeneration trough transcriptomic and metabolomic - Chang Liu; Dalong Zhu; Junlong Xue; Alimu Tulahong; Tuerganaili Aji (Scientific Reports)
Abstract Liver regeneration is a complex process crucial for recovery after partial hepatectomy (PH) or ex-vivo liver resection and autotransplantation (ELRA). This study aimed to explore the molecular mechanisms involved in liver regeneration by analyzing peripheral blood samples from three patients with alveolar echinococcosis undergoing PH and ELRA. Peripheral blood samples were collected from three patients undergoing PH and three patients undergoing ELRA at three time points: pre-operation, postoperative day 1, and postoperative day 5, as well as three healthy controls. Transcriptomic analysis was performed to identify differentially expressed genes (DEGs) using RNA sequencing, while metabolomic analysis was conducted using untargeted liquid chromatography-mass spectrometry (LC–MS). Key findings were validated through real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot analysis. Transcriptomic analysis revealed 3574 DEGs on post-operative day 1 compared to pre-operation in the ELRA group, and 3269 DEGs on post-operative day 5 compared to day 1. In the PH group, 1619 DEGs were identified on post-operative day 1 compared to pre-operation, and 896 DEGs were found on post-operative day 5 compared to day 1. Among these, 36 common genes were shared between both groups, primarily enriched in metabolic pathways. Integration of common genes, co-expression network analysis and Mfuzz clustering identified KLF14 as a gene correlated with liver regeneration processes, with its association with the PI3K-AKT pathway. Metabolomic analysis highlighted differentially expressed metabolites associated with lipid, amino acid, and energy metabolism. This study provides new insights into the molecular regulation of liver regeneration, identifying KLF14 and associated metabolic processes. These findings offer potential therapeutic targets for enhancing liver repair.